(3COH GdcGJHs - (3YHO Gddg Hf eSde Hf bJjHI GdOjnfnhQqj, CHh eMeO, GHf obnJrjnHI, J (B276 (3g` s
(3ChdgG (B:s
(3bGd CHh eMeO YHO Gddg CeG HYO MeO Gddg HLejY eMGeOg hGdKfGA Ydjg HeG gh hCgdg , hGdUdGI Ydi QShdg GdeUWai hBdg , aEfi QCjJ CcKQ Cgd ReGffG Yf SHjd s
(3BNQgG (B:s
(3CHh RjO bGd hGdcdGHjhf jaJMhf hjMjF eUOQ EaJYdJ Ydi EaJYGd , fMh EbJJGdkG , hEMJSHJ s
(3GdfSNI HgG MhGTs
(3HChdgG Jedjc bOjes
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B137s
(3JHUQGJ GdCUd (B:s
(3GdfSNI eHJhQI GdBNQ s
Keywords: (3GdCOHs